A Bahasa Melayu version (HSOPSC-BM) evaluation of patient safety culture in public hospitals in Malaysia: A multicentre assessment / Safaridah Anuar - Safaridah, Anuar (2019)
Introduction: Implementation of patient safety culture in an organization with the aim to improve patient safety outcome has received worldwide attention. Patient safety also reflects quality care in general. As patient safety continues to be a concern especially in hospital care, safety culture is a target for patient safety improvements as recommended by the Institute of Medicine. In this study, Hospital Survey on Patient Safety Culture questionnaire was used to evaluate patient safety culture in public hospitals in Malaysia. Methodology: This study was divided into two phases. Phase one was testing the validity and reliability of HSOPSC-Bahasa Melayu (HSOPSC-BM). It was a cross sectional survey with purposive sampling and involved 700 participants. The original HSOPSC which has 12 dimensions and 42 items underwent a thorough process of validation. Confirmatory and exploratory factor analyses were assessed using Statistical Package of Social Science (SPSS version 21) and Analysis of Moment Structure (AMOS version 22). Phase two assessed patient safety culture among staff in public hospitals in Malaysia using validated HSOPSC-BM. It was a cross sectional study with 700 participants who were selected from four hospitals using quota sampling. Descriptive analysis was done followed by inferential analysis using SPSS. Three outcome measures which were patient safety score, patient safety grade and number of events reported were investigated for its relationship with safety culture dimensions using regression analysis. Result: The Content Validity Index was excellent (CVI-0.9). A final 9 dimensions and 30 items were retained in the hypothetical model of HSOPSCBM. Results of goodness of fit for the hypothetical model were of χ2 (df) of =770(369) with p value of <0.005, CFI=0.8, RMSEA=0.7 and P ratio=0.85.The overall Cronbach’s iv Alpha for the new construct is 0.88. In Phase two of the study, 89% of participants gave valid responses. Among safety culture dimensions, Organizational Learning scored the highest with 87% positive response rate whilst Non-Punitive Response to Error scored the lowest with 4.3%. In regression analysis testing mean patient safety score showed that medical officers are 4.9 times more likely to practice safety culture compared to other profession and socio-demographic and job related characteristics [OR 4.87 (95% CI: 1.31, 18.15, p<0.05)] Similarly, medical officers were 2.3 times more likely to report 1-2 incidence reporting compared to other groups (OR 2.33 [1.23,4.41], p<0.05) Discussion/Conclusion: In the Phase 1 study, HSOPSC-BM didn’t replicate similar construct as the original HSOPSC. However, it was considered appropriate for use in the Malaysia healthcare setting. In phase two, it was noted patient safety practice requires a lot of improvements. Medical officers are practising safety culture better than other profession or socio-demographic and job-related characteristics. In conclusion, patient safety culture should be introduced into medical curriculum to educate students before they embark into their real career. Implementation of remedial measures based on findings from patient safety surveys using HSOPSC-BM could improve the quality of health services in Malaysia.